Thickness of preperitoneal fat as a predictor of malignancy in overweight and obese women with endometrial polyps - CIAVATTINI, ANDREA (Oncol Lett, 2016)
The aim of the present study was to determine the association between the thickness of preperitoneal fat (PFT), utilized as an indicator of visceral fat deposition, and the risk of premalignant and malignant changes of endometrial polyps (EPs) in overweight and obese women. Overweight and obese women who had undergone diagnostic outpatient hysteroscopy and subsequent endometrial polypectomy between January 2010 and May 2013 were analyzed. Each patient underwent a transabdominal ultrasound for the purpose of measuring the thickness of preperitoneal fat. A total of 146 overweight or obese women were analyzed. The overall incidence of malignant or premalignant lesions was 8.2%. Notably, 5 patients (3.4%) received a histopathological diagnosis of complex hyperplasia with atypia, while polyps harboring carcinoma were diagnosed in 7 cases (4.8%). A significantly increased PFT was observed in women exhibiting preneoplastic and neoplastic lesions, compared with women with benign EPs (mean ± SD, 23.2±3.7 vs. 15.9±8.3; P<0.01). Patient age of >60 years was significantly associated with malignant progression of EPs, while body mass index, menopausal status, arterial hypertension, diabetes, abnormal uterine bleeding, hormone replacement therapy and tamoxifen treatment demonstrated no significant association with the development of preneoplastic and neoplastic lesions of the endometrium. In a multivariate analysis, only PFT maintained a significant correlation with the diagnosis of preneoplastic and neoplastic lesions on EPs (odds ratio, 1.14; 95% confidence interval, 1.04–1.26). Ultrasound evaluation of PFT in overweight and obese women may be useful for the identification of a particularly high-risk subgroup of women. Therefore, regardless of symptoms or additional clinical variables, these particularly high-risk women require appropriate counseling and prompt surgical removal of EPs.